The Role of Islamic Religious Education Teachers in Inculcating Character Values in Students at SMP Negeri 4 Persiapan Blangkejeren - Wati, Ely (Jurnal Profesi Guru Indonesia, 2024)
The approach of Islamic Religious Education teachers has a great role in instilling the character values ​​of their students, the teacher has a strategic position as the main actor. The attitude and behavior of a teacher leaves a deep impression on the student, so that the character and personality of the teacher becomes a mirror of the student. teachers have a great responsibility in producing a generation with character, culture and morals. There are still many students who have not been able to apply character values ​​in the school environment or at home. For this reason, the writer was interested in choosing a title about the role of Islamic Religious Education teachers in instilling the character values ​​of class VIII students of SMPN 4 Preparation Blangkejeren, Gayo Lues. This research aims to find out the role of Islamic Religious Education teachers in instilling character values ​​in students to find out the methods, supporting factors and obstacles encountered in instilling character values ​​in SMPN 4 Preparatory Blangkejere, Gayo Lues, especially class VIII. This type of research is Field Research, which is research that requires the researcher to go to the 'field' to observe a phenomenon in a natural state. The data sources used are primary data sources and secondary data sources. Data collection methods are interviews, observations and documentation. While the data analyst technique used is inductive through data reduction, data presentation (data display) and conclusion (verification). The conclusion obtained is that the role of Islamic Religious Education teachers in instilling character values ​​in students can be through group activities with the hope of applying the character of discipline and responsibility. In addition to the application of 7s (smile, greeting, hello, polite, polite, patient and grateful). The methods used in instilling character values ​​can be through exemplary methods, advice methods, demonstration methods, and discussion methods. A supporting factor in instilling character values ​​is the existence of facilities and infrastructure that support and media telling stories. whereas the inhibiting factors in instilling character values ​​include the busyness of parents, the environment, and the mass media. Further, the solution to overcome obstacles in instilling character values ​​is the assignment of tasks and cooperation between teachers and parents